Topologia das funções entrópicas - Kurashima, Keoma Hermenegildo; Oler, Juliano Gonçalves (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2024)
In basic Physics courses, students come into contact with the second law of thermodynamics, which leads them to define a new state function called “entropy”. However, the definitions came from empirical studies. We will show in a generalized way the Ludwig Eduard Boltzmann formulation for entropy, in addition to some topological properties of the set of entropic functions.